Digital Tourism: A Content Analysis of West Java Tourism Websites - Fajar Kusnadi Kusumah Putra; Pudin Saepudin; Edwin Adriansyah; I Gusti Agung Wahyu Adrian (Program Pascasarjana, 2018)
Digital tourism is one of three strategic priorities from Ministry of Tourism to increase the number of tourists who visit Indonesia. Tourism industry is one of the successful sector using Internet media to share destination images, where the tourism websites become a very useful tool to promote tourism by giving important informations for visitors. This study explores the effectiveness of official tourism websites in West Java province, Indonesia. Content analysis method, consist of three dimensions: Aesthetic (destination visualization, websites design); Informative (uniqueness, monetary value, and cultural promotion); Interactive (e-travel planner, online communities) were used to assess 29 official cities and regency’s tourism websites. The results presented in this paper showed that West Java tourism websites were found to be generally fair in one dimension but lacked to attracted visitors. Based on the result findings, it is recommended that the official tourism organizations should evolve their websites as the marketing tools and the most important for delivering positive images of the destination online. These research give implications for the local tourism websites administrator to improve the website’s content and also further research in tourism websites evaluation.Keywords: Content analysis, digital tourism, website’s evaluation, west java tourism.